Reintegration of Ex-Prisoners Into Village Environment - Knežić, Branislava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
Each society, as well as persons who have served their sentences in penal institutions, is faced with the problem of ex-prisoners coming out of prison. They are not well accepted by the environment, nor can they easily integrate into it. The success of institutional treatment, whatever it is, is verified through their behaviour as free persons. The high percentage of recidivists doesn't support the story of socialisation success. As mentioned above, they adapt more successfully to prison and return more readily to that well-known environment rather than to probe "prison treatment" on a long track outside of prison walls. The problem of reintegration and recidivism can not be examined without a thorough investigation of ex-convict personalities and recognition of the social environment. Besides general social conditions, the crucial role has family conditions and also social, economic and cultural conditions (family stability, material circumstances and living accommodation, structure of local groups and environment where they return to). We suppose that undamaged family relations, the possibility of working on their own estate and the hospitality of the rural environment can ease the acceptance of the stigmatised prisoner and his resocialization to changes in society and the village. Social pathology (alcoholism, drugs, gambling, begging, prostitution), poverty, unemployment, crisis and socio-economic changes, as well as neglected villages and estates, can influence disorientation in these adverse circumstances.